Analisis Profitabilitas (Return on Asset dan Return on Equity) pada PT Sido Muncul Tbk periode tahun 2015-2018 - Malika Awliya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2022)
This study was conducted with the aim of determining how profitability develops using the ratio of return on assets (ROA) and return on equity (ROE) at PT Sido Muncul Tbk. The data used in this study is data from the financial statements of PT Sido Muncul Tbk for the 2015-2018 period. In this study, the return on assets of PT. Sido Muncul Tbk seems to have experienced quite optimal, effective and efficient results from 2015 to 2018. Thus, it can be said that the company's ability to manage resources to make a profit can be considered a success. As for the calculation of return on equity at PT Sido Muncul Tbk for the 2015-2018 period, it can also be said that it has seen good developments. Thus, the company's efforts in using its capital to obtain profits are optimal.